PATIENT-REPORTED VISUAL FUNCTION FROM THE OCRIPLASMIN FOR TREATMENT FOR SYMPTOMATIC VITREOMACULAR ADHESION, INCLUDING MACULAR HOLE (OASIS) STUDY. Issue 7 (July 2020) - Mein, Calvin; Dugel, Pravin U.; Feiner, Leonard; Drenser, Kim; Miller, Daniel; Benz, Matthew; Meunier, Esmeralda; Moro, Lionel; Fineman, Mitchell S.
Abstract : Purpose: To evaluate patient-reported visual function after ocriplasmin through the 25-item National Eye Institute Visual Function Questionnaire (VFQ-25) in patients with symptomatic vitreomacular adhesion/vitreomacular traction including macular hole. Methods: This was a prespecified analysis of a secondary endpoint from the OASIS trial. Patients received a single intravitreal injection of ocriplasmin (0.125 mg) or sham and completed the VFQ-25 questionnaire at baseline and at Months 6, 12, and 24. Clinically meaningful (≥5-point) changes from baseline were assessed. Results: Of the 220 patients enrolled, 146 received ocriplasmin and 74 received sham. At Month 24, the percentage of patients with a ≥5-point improvement from baseline in VFQ-25 composite scores was higher with ocriplasmin versus sham (51.4% vs. 30.1%, 95% confidence interval, 8.1–34.5, P = 0.003). The percentage of patients with ≥5-point worsening at Month 24 was lower with ocriplasmin versus sham (9.5% vs. 15.6%, 95% confidence interval: −15.6 to 3.5, P = 0.191). A larger percentage of patients treated with ocriplasmin versus sham experienced a ≥5-point improvement in VFQ-25 composite and subscale scores at Month 24 regardless of baseline full-thickness macular hole status. Conclusion: A larger percentage of patients with symptomatic vitreomacular adhesion/vitreomacular traction reported clinically meaningful improvements in self-assessed visual function with ocriplasmin than sham. Abstract : Supplemental Digital Content is Available in the Text.Symptomatic vitreomacular adhesion is associated with reduced visual acuity, which can significantly affect quality of life. This study was a prespecified analysis of the 2-year, sham-controlled OASIS trial. Clinically meaningful (≥5-point) changes in patient-reported outcomes were assessed. Ocriplasmin resulted in clinically meaningful improvements in visual function.